Brake Performance Maps for a Cu-Free Friction Material with Different Scorching Conditions. Issue 3 (4th May 2021) - Candeo, Stefano; Federici, Matteo; Leonardi, Mara; Straffelini, Giovanni
Abstract: A Cu-free brake friction material was produced with three surface scorching conditions, and the brake performance was compared using maps of the friction coefficient, maximum disc temperature, and deceleration. The tests were carried out using a subscale dynamometer to avoid any influence of hardware on the obtained brake data. The friction coefficient decreased with velocity and contact pressure and as the intensity of the scorching treatment increased. As a consequence, the material with intermediate scorching showed the most stable coefficient of friction throughout the different brake conditions (10–80 bar; 40–200 km/h). The brake decelerations were found to strongly increase with pressure and, depending on the scorching condition, to slightly decrease when the velocity was increased. The specific wear rates were evaluated for specific brake sections and were found to be dependent on the scorching treatment, which must be properly designed to optimize the brake performance of the tribological system.